Constraint analysis of the farmers on climate variability in castor (Ricinus communis L.): CONSTRAINT ANALYSIS OF THE FARMERS ON CLIMATE VARIABILITY IN CASTOR - P ARCHANA; M JAGAN MOHAN REDDY; I SREENIVASA RAO; G D S KUMAR (Journal of Oilseeds Research, 2013)
Castor (Ricinus communis L.) is cultivated extensively in Mahaboobnagar district of Andhra Pradesh because of the commercial importance ofits oil. The area and production of castorin Mahaboobnagaris gradually decreasing for which one of the most important reasons is the high incidence of botrytis greyrot disease due to conducive climate variations. Apart from this, the frequent droughts in the region also influence in reduction of area. Keeping this in view the present study was carried out to understand the problems and suggestions as perceived by farmers on adaptation to climate variability in castor. The results indicated that high incidence of botrytis disease in rainy season, lack of training on climate variability coping mechanisms were some of the problems. Development of cultivars resistant to botrytis disease with short stature and profuse branching, providing training to farmers and extension officials on techniques of crop production and adaptation options to face the climate variability in castor were some of the perceived suggestions. Based on the results a strategy was developed to enhance the adaptability of castor farmers towards climate variability.